2014
DOI: 10.1149/2.0321412jes
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Water Interactions with Gas-Diffusion-Layer Surfaces

Abstract: Understanding dynamic liquid-water uptake and removal in gas-diffusion layers (GDLs) is essential to improve the performance of polymer-electrolyte fuel cells and related electrochemical technologies. In this work, GDL properties such as breakthrough pressure, droplet adhesion force, and detachment velocity are measured experimentally for commonly used GDLs under a host of test conditions. Specifically, the effects of GDL hydrophobic (PTFE) content, thickness, and water-injection area and rate were studied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 51 publications
(118 reference statements)
12
101
0
Order By: Relevance
“…The decrease in simulated current density with decreasing temperature is likely due to the two phase model used for the catalyst layer and catalyst layer-GDL interphase. Another potential mechanism for the 2 AEX1 discrepancy at low temperature is the assumption in the simulation that the reactant flow channels remain free of liquid water [34]. The difference in low temperature performance between the 1 and 2 AEX1 simulations is easy to discern when looking at the liquid-water profiles in the anode and cathode GDLs.…”
Section: Model Simulation Results and Discussionmentioning
confidence: 99%
“…The decrease in simulated current density with decreasing temperature is likely due to the two phase model used for the catalyst layer and catalyst layer-GDL interphase. Another potential mechanism for the 2 AEX1 discrepancy at low temperature is the assumption in the simulation that the reactant flow channels remain free of liquid water [34]. The difference in low temperature performance between the 1 and 2 AEX1 simulations is easy to discern when looking at the liquid-water profiles in the anode and cathode GDLs.…”
Section: Model Simulation Results and Discussionmentioning
confidence: 99%
“…In case of O4, where the lowest TP liquid permeability of the repetition unit domains was identified and the highest pressure drop can be expected, the pressure drop for a liquid water flow rate equivalent to a current density of 3 A/cm 2 is just about 5 Pa. Such low pressure drops are three orders of magnitude away from breakthrough pressures 22,27,44 or pressures that are required for in-plane growth after breakthrough under a rib-structure for Toraytype GDL. 44 Santamaria et al 22 reported similar post-break-through liquid permeabilities of 0.5 × 10 −12 m 2 for Toray TGP-H-030 and TGP-H-060 papers with 5 wt% PTFE that were obtained from liquid water imbibition experiments.…”
Section: Journal Of Thementioning
confidence: 91%
“…If the direction of the flux of water is into the GDL, then a no-flux boundary condition is set. In several simulations reported herein, P L was set higher than P G at the CH|GDL boundary to simulate a GDL with a higher droplet adhesion force, 40 although the same allowance for only fluxes out of the GDL in the liquid phase was maintained. It is well known that droplets along this interface results in higher dynamic liquid pressures before the droplet is removed.…”
Section: −βτmentioning
confidence: 99%
“…This droplet detachment is strongly coupled to the adhesion force of the material on the GDL surface. 40,41,46,78,79 Incorporation of this physics into continuum cell models remains a challenge. 9 However, such effects should essentially impact the water liquid pressure at the boundary, which is the pressure of the droplet at detachment, assuming Darcy's law remains valid.…”
Section: Impact Of Catalyst-layer Thickness-as Shown Inmentioning
confidence: 99%